Association between Serum Total Testosterone Level and Bone Mineral Density in Middle-Aged Postmenopausal Women - JinXiao Yang; Guofei Kong; Xiaocong Yao; Zhongxin Zhu (International Journal of Endocrinology)
Background. Hormone status strongly affects women’s health and quality of life. To date, studies investigating the association between total testosterone (T) level and bone mineral density (BMD) in women are limited and have yielded contradictory conclusions. The aim of our study was to examine the association between serum total T level and lumbar BMD in postmenopausal women aged 40–59 years. Methods. The study group included 1,058 women from the 2011–2016 National Health and Nutrition Examination Survey. Multiple regression analyses were used to evaluate the association between serum total T level and lumbar BMD. Results. After adjusting for covariates, there was a positive association between the serum total T level and lumbar BMD (β, 1.07; 95% confidence interval, 0.17–1.97). A non-linearity in this association was identified, with a point of inflection at 30 ng/dL. Conclusions. Serum total T level was positively associated with lumbar BMD in middle-aged postmenopausal women up to a T level >30 ng/dL. Therefore, increasing T level in women with a low serum total T level may have beneficial outcomes on bone health.